Alcohol-Induced Hyperosmolar Hyperglycemic State in Type 1 Diabetes Mellitus: A Case Report - I Dewa Ayu Agung Diah Sutarini; Romy Windiyanto (HM Publisher, 2023)
Background: Adolescents with diabetes mellitus who consume alcohol increase the risk of developing diabetic ketoacidosis (DKA) and HHS. In addition, alcohol consumption has long-term adverse effects on the glycemic control of type 1 diabetes mellitus. This study aimed to describe cases of alcohol-induced hyperosmolar hyperglycemic state in adolescents with type 1 diabetes mellitus. Case presentation: A teenage boy, aged 15 years, came with his family to the ER with complaints of weakness. The patient also complained of persistent tingling in the legs for the last two weeks. Three days before entering the hospital, the patient also felt blurred vision that disturbed him while studying at school. The results of the physical examination stated that the general condition was weak, compos mentis, pulse 80x/minute, blood pressure 110/70 mmHg, respiratory rate 20x/minute, axillary temperature 36ºC, weight 65 kg, and height 165 cm. Examination of the extremities showed a slow return of skin turgor. Laboratory evaluation showed an increased leukocyte count (10.45x103/μL), and blood gas analysis showed mild acidosis (HCO3 24.3 mmol/L, PCO2 38.6 mmHg, PO2 82 mmHg, tCO2 26 mmol/L, pH 7.4, and SaO2 96%), HbA1c 14.2%, glucose at 621 mg/dL (hyperglycemia), C-peptide 0.87 ηg/dL. The patient was diagnosed with hyperglycemia, hyperosmolar state, type 1 diabetes mellitus, and mild dehydration. Conclusion: The main management of alcohol-induced hyperosmolar hyperglycemic state in type 1 diabetes mellitus is fluid resuscitation to achieve hemodynamic stability, correction of electrolyte abnormalities, gradual reduction of blood sugar levels, and hyperosmolality. Insulin administration to lower blood sugar levels is done after stable hemodynamics.